Tunisia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1997)
This Selected Issues paper serves as background to the 1997 Article IV Consultation with Tunisia and sheds light on economic developments in Tunisia during 1990-96. The paper aims to identify more closely obstacles to higher growth and to draw lessons from past experience to help formulate the economic strategy for the coming years, taking into account the prospective evolution of the exogenous environment. The paper also reviews issues related to the further integration of Tunisia into world markets.